Evaluation of Selected Aqueous Plant Extracts for the Management of Helicoverpa armigera (Hubner) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
The focus in this study is the investigation of the insecticidal potential of different water-based plant extracts against the pathogen Helicoverpa armigera, of which the specific attention is given to LC50 values, suppression of larval population, improved yield in tomato, and overall economic feasibility. It was observed that considerable variation was found both among and within plant species during the experimental trials. It was also found that the strongest activity was in fact recorded for Azadirachta indica (LC50 = 0.081%), while Calotropis gigantea (LC50 = 3.244%) and Pongamia pinnata (LC50 = 3.835%) also exhibited notable toxicity. Observation of the plant parts found that Pedalium murex roots were particularly potent. On the other hand, Vitex negundo appeared less effective in LC50 assays (4.231%), yet demonstrated high performance under real field conditions. Field experiments provided further confirmation. Treatments with Ipomoea carnea and V. negundo reduced larval counts per ten tomato plants from 2.43 to 0.52 and 0.59, respectively. When these two species were applied in combination, the reduction was even greater, with larval density dropping to 0.23. The resultant observation has highlighted a synergistic interaction between the species. Results on the yield assessments has revealed crop productivity gains of up to 32%, with Pteridium aquilinum and Homalomena arifolia showing the strongest positive impact. Economic analyses has reinforced these findings where favorable cost–benefit ratios were achieved, particularly with C. gigantea and V. negundo. In these plants, returns exceeded 1:1.8. Taken together, the results emphasize the dual agronomic and economic promise of botanical insecticides. The results in this study are similar to a previous observation that recommend their use as part of integrated pest management programs. A further understanding of the mechanistic insights hinted that larval mortality is linked to immune responses triggered in H. armigera by phytochemicals present in the extracts.
Keywords: Helicoverpa armigera; Botanical insecticides; Aqueous plant extracts; Integrated pest management (IPM); Cost–benefit analysis